Papua dalam semiosfer Kota Yogyakarta - Bagus Ajy Waskyto Sugiyanto (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
This paper aims to find out how the semiosphere boundary is defined for Papuan students in Yogyakarta. The nickname of the city of Yogyakarta as a miniature of Indonesia actually needs to be questioned again. The unfavorable relationship between the Yogyakarta community and Papuan students recently required a study of cultural meaning to be able to find out the root of the problem. By using Juri Lotman's model of cultural semiotics, this study finds the boundaries that are central and peripheral to the Yogyakarta semiosphere. Analysis of the Yogyakarta semiosphere boundary shows that there are forms of marginality among Papuan students. Papuan students are still in outer space or peripherals in the Yogyakarta semiosphere, while the core is the symbols of "Indonesian and Javanese".